2015
DOI: 10.1155/2015/601767
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity-Related PKMζSignaling in the Insular Cortex Is Involved in the Modulation of Neuropathic Pain after Nerve Injury

Abstract: The insular cortex (IC) is associated with important functions linked with pain and emotions. According to recent reports, neural plasticity in the brain including the IC can be induced by nerve injury and may contribute to chronic pain. Continuous active kinase, protein kinase Mζ (PKMζ), has been known to maintain the long-term potentiation. This study was conducted to determine the role of PKMζ in the IC, which may be involved in the modulation of neuropathic pain. Mechanical allodynia test and immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…Studies have shown that the IC has an important role in the pain modulation process 5 , 49 and consists of multiple neurotransmitter systems related to pain, including cannabinergic, opioidergic, serotoninergic, and dopaminergic transmissions. 50 , 51 Moreover, previous studies demonstrated a significant increase in both mRNA and protein expression levels of CB1R, TRPV1, and NAPE-PLD in the dorsal root ganglion of neuropathy rats during the development or maintenance of pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the IC has an important role in the pain modulation process 5 , 49 and consists of multiple neurotransmitter systems related to pain, including cannabinergic, opioidergic, serotoninergic, and dopaminergic transmissions. 50 , 51 Moreover, previous studies demonstrated a significant increase in both mRNA and protein expression levels of CB1R, TRPV1, and NAPE-PLD in the dorsal root ganglion of neuropathy rats during the development or maintenance of pain.…”
Section: Discussionmentioning
confidence: 99%
“…The insular cortex (IC) is an important region of brain associated with the processing of painful stimuli and emotion. 5 The pain matrix, including the IC, is activated by noxious electrical and chemical stimulation, and acute and chronic pain stimulation, as demonstrated by functional magnetic resonance imaging. 6 8 Moreover, lesions of the IC diminish NP-related behaviors in animal models of NP.…”
Section: Introductionmentioning
confidence: 99%
“…PKMzeta has been reported to interact with GluR1 to maintain LTP in the ACC [ 27 ], a key brain region involved in the affective components of pain [ 15 , 45 ]. The blockade of PKMzeta significantly reduces the postsynaptic GluR1 insertion in ACC neurons following a peripheral nerve injury [ 25 , 44 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that CFA-induced mechanical and thermal hypersensitivity is reduced by the inhibition of PKCzeta/PKMzeta activity [ 26 ]. Another study demonstrated that PKMzeta may interact with GluR1 to maintain long-term potentiation (LTP) in the ACC [ 27 ] and hippocampus [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the authors did not suggest that this region alone encodes ongoing pain, as other areas were also reported as periodically active and recent animal work highlights a dominant role for the amygdala in pain unpleasantness, for example, reminding us of pain's complexity and requirement to activate many brain regions (Corder et al, 2019), several results, including the neurochemistry findings discussed above, propose that this region provides potential as a possible biomarker of nociceptive drive and pain intensity. This is perhaps supported by the failure to activate it, unlike most other pain-related brain regions, by empathy, hypnosis, or recalled pain (Fairhurst et al, 2012;Raij et al, 2005;Wager et al, 2013); it is part of the NPS and Pain-Analgesic network; predictive coding identifies its role encoding stimulus intensity (Geuter et al, 2017); it is not encoding saliency (Horing et al, 2018); and there is alteration of pain upon posterior insula modulation (acute and tonic) in animals and humans (Dimov et al, 2018;Garcia-Larrea and Mauguiè re, 2018;Han et al, 2015;Lin et al, 2017). A composite signature reflecting ongoing activity, neurochemical and network coupling changes from various brain regions, such as the dorsal posterior insula combined with other regions, would be interesting to explore in the context of a potential biomarker.…”
Section: Imaging Tonic Pain To Reveal Potential Biomarkers?mentioning
confidence: 99%